Characterization of low-cost lipase by solid-state fermentation of palm kernel cake using candida cylindracea - Elgharbawy, Amal A.M.; Alam, Md Zahangir; Mohd. Salleh, Hamzah (Asian Research Publishing Network, 2016)
This study aimed to identify the properties as well as the application of Candida cylindracea lipase produced from palm kernel cake (PKC) by solid-state fermentation (SSF). Characteristics of PKC-lipase have been investigated which include: thermal stability, pH stability, stability in organic solvents and metal ions solutions. The enzyme assays were conducted using colorimetric method and the activity was expressed as residual activity. It was revealed that the optimal temperature and pH were 37°C and 8.0, respectively. The enzyme was stable at temperature ranges of 25-45°C and pH 7.08.0 respectively.Zn 2+,Mg 2+ and Ca 2+ stimulated the enzyme while Fe 3+ inhibited its activity. The results showed that 1.0% of EDTA enhanced the lipase activity while incubation in SDS and Tween-80 resulted in the reduction of its activity.Moreover, the produced lipase exhibited some levels of stability at low concentrations of organic solvents (methanol,ethanol, 2-propanol, acetone, hexane and toluene). The application of the PKC-lipase showed promising results in hydrolysis whereas 50.48% and 45.98% of canola oil and olive oil were converted to free fatty acids (FFA), respectively. The knowledge obtained from this study can give an insight on understanding the PKC-lipase properties in order to be used in industrial and biotechnological applications, particularly in biodiesel production.